Workfare Work: The Impact of Workfare on the Worker/Client Relationship - Joel Handler (Social Work & Society, 2005)
This article details the American experience of welfare reform, and specifically its experience instituting workfare programs for participants. In the United States, the term "welfare" is most commonly used to refer to the program for single mothers and their families, formerly called Aid to Families with Dependent Children (AFDC) and now, Temporary Assistance to Needy Families (TANF). In 1996, politicians "ended welfare as we know it" by fundamentally changing this program with the passage of the Personal Responsibility and Work Opportunity Reconciliation Act of 1996 (PRWORA). The principal focus of the 1996 reform is mandatory work requirements enforced by sanctions and strict time limits on welfare receipt. While PRWORA's emphasis on work is not new, the difference is its significant ideological and policy commitment to employment, enforced by time limits. When welfare reform was enacted, some of its proponents recognized that welfare offices would have to change in order to develop individualized workfare plans, monitor progress, and impose sanctions. The "culture" of welfare offices had to be changed from being solely concerned with eligibility and compliance to individual, intensive casework. In this article, I will discuss how implementing workfare programs have influenced the relationship between clients and their workers at the welfare office. I start by describing the burdens faced by offices even before the enactment of welfare reform. Local welfare offices were expected to run programs that emphasized compliance and eligibility at the same time as workfare programs, which require intensive, personal case management. The next section of the paper will focus on strategies welfare offices and workers use to navigate these contradictory expectations. Lastly, I will present information on how clients react to workfare programs and some reasons they acquiesce to workfare contracts despite their unmet needs. I conclude with recommendations of how to make workfare truly work for welfare clients.